The Network Structure of Adolescent Well-Being Traits: Results From a Large-Scale Chinese Sample - Zeng, Guang; Peng, Kaiping; Hu, Chuan-Peng (Frontiers in Psychology, 2019)
Background. The mental health and well-being of adolescents are becoming increasingly important globally. Understanding the relationship between different aspects of well-being is crucial for effective interventions of the well-being of adolescents. The present study aims to analyze the network structure of adolescent well-being and identify the central well-being traits. Methods. We used a network model to analyze the network structure of a psychometrically sound measurement of adolescent well-being ---- the engagement, perseverance, optimism, connectedness, and happiness (EPOCH) scale. The dataset comes from a representative sample of Chinese adolescents (17, 854 participants from rural and urban areas from Southern, Northern, and the middle part of China). Results. The twenty items of EPOCH formed a highly interconnected network. The item H4 (“I am a cheerful person.”), E2 (“I get completely absorbed in what I am doing”), and O4 (“I believe that things will work out, no matter how difficult they seem”) were the most central traits. Conclusions. Cheerfulness, engagement in current activity and optimism for the future are most central to the psychological well-being of Chinese adolescents. Future studies should further test the dynamics between these central traits and other well-being traits to find effective interventions of well-being of adolescent.